(untitled) (Research, Society and Development, 2022)
In Brazil, most of the groundwater is extracted by tube wells where large flows are taken and are usually used by industries, commerce, condominiums, among others. The grant is the legal instrument responsible for ensuring the quantitative and qualitative control of water uses, as well as guaranteeing the rights of access to water. Thus, this work aims to quantitatively evaluate the grants of groundwater resources in the municipality of Itabira (MG), seeking to know the water availability for the granted users. For this, a documental research was carried out, based on the analysis and evaluation of hydrogeological data from the information on the granting processes available on the Integrated Environmental Information System (SIAM) platform. It was found that most of the grants were issued for human consumption, however they represent the smallest volumes used. On the other hand, the largest volumes granted (about 80% of the total) are destined for mining activities. Regarding water availability, the waters obtained from the rocks of the Borrachudos Suite, the Guanhães Complex and the Granite-Gneissic Complex, are responsible for almost all the flow extracted in the municipality of Itabira, presenting good conditions for water storage. The importance of preserving groundwater is highlighted, since wells with expressive flows have large volumes of water granted, in the municipality of Itabira they are intended for mining purposes.